Statistical differences and biological implications : a comparative analysis of the advertisement calls of two Andean stream treefrogs (Hylidae: Hyloscirtus) and the evolution of acoustic characters (2017)
ABSTRACT: We describe and compare the advertisement calls of Hyloscirtus antioquia and H. larinopygion, two sibling species of the Andean stream treefrogs of the Hyloscirtus larinopygion group. We recorded individual calls at seven localities in Colombia, including the type locality of H. antioquia. The advertisement calls of both species consist of a single, low-pitched, multi-pulsed note, with some overlaps in frequency and the duration of pulses (dominant frequency 1642.7– 1756.5 Hz and 5–6 periodic pulses in H. antioquia and 1722.7–1894.9 Hz and 5–6 periodic pulses in H. larinopygion). We found significant statistical differences in spectral and temporal variables between both species; however, no acoustic trait can be considered diagnostic. Our results highlight an important topic in evolutionary biology that deserves thorough examination in Andean anurans; because not all statistically significant differences in auditory signals matter in male recognition and speciation. Furthermore, in the context of the most comprehensive phylogenetic hypothesis available for Hyloscirtus, the optimisation of acoustic characters suggests that call structure has a complex history that involved multiple transformations.